Centrosome amplification as a possible marker of mitotic disruptions and cellular carcinogenesis in multiple myeloma - Dementyeva, E; Nemec, P; Kryukov, F; Muthu Raja, K R; Smetana, J; Zaoralova, R; Greslikova, H; Kupska, R; Kuglik, P; Hajek, R (Leukemia research, 2010)
Centrosome amplification (CA) as a potential marker of mitotic disruptions in multiple myeloma (MM) was investigated in two populations of B-cell lineage: B-cells and plasma cells (PCs). Using immunofluorescent staining, it was shown that CA in B-cells is present in 3.2+/-2.5% in healthy donors versus 9.9+/-7.9% in MM patients (p<0.0001). Based on the calculated threshold value of CA in B-cells, 37% (14/38) of MM patients were positive. There was no significant correlation between CA-positive MM cases (based on PC samples evaluation) and the occurrence of cytogenetic abnormalities in PCs, including del(13)(q14), del(17)(p13), gain(1)(q21) and hyperdiploidy.
Keywords: senioři; plazmatické buňky; senioři nad 80 let; Multiple Myeloma; hybridizace in situ fluorescenční; Prognosis; Middle Aged; mitóza; karyotypizace; mužské pohlaví; Adult; Karyotyping; In Situ Hybridization, Fluorescence; Mitosis; Aged, 80 and over; B-lymfocyty; mnohočetný myelom; ženské pohlaví; prognóza; B-Lymphocytes; fluorescenční protilátková technika; Humans; Plasma Cells; Centrosome; lidé středního věku; Fluorescent Antibody Technique; centrozom; dospělí; Female; Aged; lidé; Male